EL alto comercio de Valparaíso y las grandes casas extranjeras, 1880-1930. Una aproximación - Couyoumdjian, Juan Ricardo (Historia, 2000)
This article provides an overview of the role of the foreign commercial houses of Valparaiso in the economic life of Chile during the first decades of the 20th century. Specific reference is made to their corporate structure, their role in the overseas trade of the country, their trading and agency businesses; their importance in nitrate and foreign exchange, their links with the nascent Chilean industries and the institutions that bound them together. Their decline after 1930 was due in part to the changes in the economic and political conditions of Chile, but also to their limited capital in relation to the size and requirements of the new mining and industrial sectors.